Dinamika Habitus dan Modal dalam Hara: Analisis Struktur Sosial Pierre Bourdieu terhadap Tiga Cerpen Najib Mahfuz: The Dynamics of Habitus and Capital in Hara: Pierre Bourdieu's Social Structure Analysis of Three Short Stories by Najib Mahfuz - Zaid, Muhammad; Buana, Cahya; Mawardi , Mawardi; Daulay, Heeral Manna; Faiz, Mohammad (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the dynamics of complex social structures in Najib Mahfuz's literary works through the lens of Pierre Bourdieu's sociological approach to literature. The background of this study is based on Hara's central position in Mahfuz's narrative, which serves as a microcosm of Egyptian society, marked by value conflicts and power struggles. Using a qualitative descriptive method with a textual approach, this study dissects three selected short stories: "Zakirat al-Jiran" (Memories of Neighbors), "Al-Hutaf" (The Call), and "Sada al-Nisyan" (Echoes of Forgetfulness). The analysis specifically applies Bourdieu's triadic concept of Habitus, Capital (economic and Symbolic), and Field, or Arena, to uncover the hidden mechanisms of domination. The study's results reveal diverse manifestations of social structures. "Zakirat al-Jiran" depicts the phenomenon of hysteresis of habitus, where conflicts continue to be reproduced blindly despite the loss of their historical roots, indicating the stagnation of tradition. "Al-Hutaf" highlights the violent clash between Economic Capital and Symbolic Capital, where the moral integrity of society successfully resists the wealth obtained from corruption, proving that social legitimacy cannot always be bought with money. Finally, "Sada al-Nisyan" criticizes the cycle of tyranny; the return of the main character's cruelty after amnesia proves that changes in individual behavior are meaningless without a transformation of the structure of the power arena itself. In conclusion, Mahfouz describes a social structure that is resistant to change, where the position of social agents is largely determined by the accumulation of symbolic capital and habitus that have been firmly institutionalized in society.